STUDI EFEKTIVITAS PENGELOLAAN KOLABORATIF KAWASAN PERAIRAN TAMAN NASIONAL BALI BARAT TERHADAP TUTUPAN KARANG HIDUP DAN SOSIAL EKONOMI MASYARAKAT LOKAL - Iwan Dewantama, Made; Mardani, N.K.; Windia Adnyana, I.B. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 2 No 2, 2012)
Natural conservation management is a very important task that not only aims to save the environment but alsosupport the people that live in it. All variables of life become part of the management goal which often blurs the phasesof management processes towards an effective one. This study aims to measure the effectiveness of conservationmanagement of West Bali National Park (TNBB) based on measured indicators.The methods of measuring effectiveness is based on several indicators (biophysical, socio-economics andgovernance) using the LIT (Line Intercept Transec) method to monitor coral reefs on 8 diving sites in TNBB. Thesocio-economics and governance indicator utilize questionnaire method and discussions with a sample of localcommunity selected randomly from 4 villages around the TNBB zone.The biophysical indicator demonstrate that the amount of coral reef cover in TNBB is 37,1% which falls underthe MEDIUM category. Meanwhile, the socio-economic indicator illustrates that the community relies very little onmarine resources and have an adequate understanding of conservation efforts and sustainable use of naturalresources. Governance indicator shows that stakeholders involvement is proceeding well with a good level ofsatisfaction regarding collaborative management process.Collaborative management of TNBB waters is quite effective in conserving coral reef ecosystem, which is builtfrom awareness, ownership and stakeholder commitment through a cooperation of various organizations called ForumKomunikasi Masyarakat Peduli Pesisir (FKMPP).
Keywords: coral reefs, socio-economics, effectiveness, collaborative